Optimized solvothermal synthesis of LiFePO4 cathode material for enhanced high-rate and low temperature electrochemical performances. (20th December 2017) - Huang, Xiaopeng; Zhang, Keyu; Liang, Feng; Dai, Yongnian; Yao, Yaochun
Abstract: A series of LiFePO4 nanoparticles were synthesized via solvothermal method for process parameters optimizing. The influences of Li:P:Fe mole ratio, reaction temperature and reaction time were systematically investigated. The obtained LiFePO4 nanoparticles were characterized by X-ray diffraction (XRD), scanning/transmission electron microscope (SEM/TEM), galvanostatic charge-discharge and cyclic voltammetry test. Results show that the mole ratio of Li:P:Fe has significant effects on the morphology and particle size of LiFePO4 material, while reaction temperature and time show little influence on crystal and shape. Prepared with Li:P:Fe = 3:1.5:1 at 180 °C for 4 h, the LiFePO4 shows rectangular nanoplates with well-dispersed, resulting in the best electrochemical performance. After carbon coating, this optimized LiFePO4 /C composite exhibits superior high-rate performance with a discharge capacity of 122.5 mAh/g at 50C at 25 °C, as well as excellent low temperature property of 116.7 and 61.4 mAh/g at 0 °C and −20 °C at 5C, respectively. To illustrate the LiFePO4 nanoparticles with different size and shape caused by variations of mole ratio, a possible formation mechanism is demonstrated. This work indicates that the optimized solvothermal process can be a promising guidance used in industrialization to synthesize cathode material with enhanced high-rate and low temperature performance. Graphical abstract: Highlights: The process parameters have been systematically investigated for solvothermal synthesis of LiFePO4 nanoparticles. The optimized LiFePO4 /C nanoplates exhibit superior high-rate performance and low temperature property. A formation mechanism for LiFePO4 nanoparticles with change of mole ratio is firstly proposed.